Assesing geodiversity in Tierra Del Fuego (Southern Patagonia, Argentina): A strategy to promote geotourism - Coronato, Andrea Maria Josefa; Schwarz, Soledad Natalia
This contribution aims to present three hierarchized areas in central and northern Tierra del Fuego (Argentina) whose geodiversity may be used for educational purposes to encourage the Earth Sciences and to design of geotourism strategies. In comparison with south Tierra del Fuego, tourism development in both areas is still low. After applying a specific methodology, 163 georesources were identified, described, mapped and classified. Fil: Coronato, Andrea Maria Josefa. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Schwarz, Soledad Natalia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego, Antártida e Islas del Atlántico Sur. Instituto de Ciencias Polares, Ambientales y Recursos Naturales; Argentina 9th International Conference on Geomorphology Atenas Grecia International Asociation of Geomorphologists